SOCIAL CAPITAL: DETERMINING A STUDENT’S E-PORTFOLIO NET WORTH - Stevens, C.; Dunlop, M. (Journal of Human Capital Development (JHCD), 2012)
Many schools or individual departments require student e-portfolios. The e-portfolios are used for different reasons including assessment, employment, internship, and/or co-op purposes. However, getting all students to “buyin” to the idea of developing an e-portfolio is a daunting challenge as most academic professionals are well aware. There is increasing concern on the part of the student that e-portfolios are not relevant for employment purposes. From the first year through the senior year, Bachelor of Science in Management (BSM) students at Wentworth Institute of Technology are required to compile an e-portfolio of their work in consultation with their academic advisor. Since 2007 we have been struggling with helping students develop professional looking e-portfolios. Over the years we switched from static built web sites, to LinkedIn, and now we are using WordPress. com. Student e-portfolios look much more professional since we made this switch. In many ways students are building social capital for themselves through the use of an e-portfolio. But, what exactly is the net worth of an e-portfolio for a student? Developing a professional looking e-portfolio goes well beyond building social capital for the student. We define net worth as it relates solely to e-portfolios. We also propose a methodology or model that can be used to determine the net worth of a student e-portfolio. We conclude by summarizing that the net worth of an e-portfolio can be broken down into heuristic patterns that add value for the student. KEYWORDS: E-portfolio, social capital, technology, educational assessment, learning, value, co-op, internship.